(untitled) (JURNAL ADMINISTRASI PUBLIK, 2022)
Abstract This study aims to determine the Strategic Management of Solid Waste Management at the Manado City Environmental Service at the Sumompo Final Disposal Site. This research uses descriptive qualitative research method with SWOT data analysis technique. SWOT analysis is carried out using the Internal Factory Analysis Summary (IFAS) and External Factory Analysis Summary (EFAS) matrices to show the current position of the organization. From the results of the data analysis, the Manado City Environmental Service is currently in a position between the Strength and Opportunity axes, namely Quadrant I (SO Strategy) where the Manado City Environmental Service has internal strengths and external opportunities. In the SWOT matrix, there are 11 strategic issues, followed by testing the level of strategic issues using the Litmus Test and through the Litmus Test there are 5 issues that fall into the strategic category, and 6 issues in the fairly strategic category. The conclusion of this research is that the Manado City Environment Service is in a very advantageous position because it is in Quadrant I (SO Strategy). Keywords: Strategic Management, Waste Management, SWOT Analysis